MARKETING IS TODAY’S TOPIC (American Journal of Technology and Applied Sciences, 2024)
This article examines the connection with market activity in furniture production enterprises: choosing a market, determining the volume of sales, planning and setting the perspective of market activity, studying market subjects, the form and methods of trading in the market.